2015
DOI: 10.1111/jfpp.12612
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Physicochemical and Nutritional Parameters of Picual and Arbequina Olive Oils during Frying

Abstract: Deep fat frying is an important cooking process in Mediterranean countries. Olive oil is a very convenient fat to use for this culinary purpose. The chemical composition of olive oils differs from edible oils in terms of fatty acid and antioxidant compounds that gives olive oil its greater stability. The aim of this work was to describe the stability of Picual and Arbequina olive oil during deep frying of frozen potatoes in comparison with high oleic sunflower oil. Changes in different physicochemical and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
(52 reference statements)
4
9
0
Order By: Relevance
“…Linoleic acid (C18:2) in the oils except SBO significantly decreased, and linolenic acid (C18:3) in SBO and POO significantly decreased from 7.3 to 7.1% and from 0.2 to 0% (p \ 0.05), respectively. These results were similar to previous studies: C18:1 and C18:2 in Picual and Arbequina olive oils and high oleic sunflower oil significantly decreased after 70 times repeated frying at 180°C [16]. C18:1 and C18:2 in canola oil significantly decreased and C16:0 and C18:0 relatively increased after frying at 185°C for 49 h [17].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Linoleic acid (C18:2) in the oils except SBO significantly decreased, and linolenic acid (C18:3) in SBO and POO significantly decreased from 7.3 to 7.1% and from 0.2 to 0% (p \ 0.05), respectively. These results were similar to previous studies: C18:1 and C18:2 in Picual and Arbequina olive oils and high oleic sunflower oil significantly decreased after 70 times repeated frying at 180°C [16]. C18:1 and C18:2 in canola oil significantly decreased and C16:0 and C18:0 relatively increased after frying at 185°C for 49 h [17].…”
Section: Resultssupporting
confidence: 92%
“…These results were similar to a previous study, reporting that L* value of virgin coconut oil decreased, and a* and b* values increased during 8 h frying [9]. However, b* value of the fresh POO was higher than the oil used 80 times repeatedly in our study, probably because the fresh POO might contain a high amount of chlorophylls and carotenoids, although their levels were not measured in this study, which in turn might be rapidly degraded during frying [16]. It was found that carotenoid content and b* value of an olive oil had a significant correlation: the more carotenoids were in the oil, the higher its b* value was [20].…”
Section: Physicochemical Properties Of the Frying Oilssupporting
confidence: 87%
“…Phenolic content dramatically decreased after the 10th frying cycle, ranging from 0% to 10% of the respective basal values; a more than 50% decrease was observed after 6 frying operations. Still, Abenoza and others () observed much lower phenolic losses; 10% and 25% Picual and Arbequina VOO phenolic content, respectively, was preserved after 70 and 63 deep‐frying cycles, respectively. Such results may, however, be attributed to the small duration time of frying cycles (3 min), which resulted in a relatively short total heating period of the oil.…”
Section: Voo Performance During Fryingmentioning
confidence: 88%
“…Tocopherol losses after pan‐frying of bread in VOO for one frying session was approximately 30% (Fisnar and others ). A 72% and 54% tocopherol loss was observed for Arbequina and Picual olive oil after approximately sixty 3‐min frying cycles of potatoes (Abenoza and others ). In general, pan‐frying has been shown to induce higher tocopherol depletion as compared to deep‐frying.…”
Section: Voo Performance During Fryingmentioning
confidence: 95%
See 1 more Smart Citation